Network Pharmacology and Molecular Docking–Based Investigation: Prunus mume Against Colorectal Cancer via Silencing RelA Expression - Zhou, Minfeng; Li, Jinxiao; Luo, Dan; Zhang, Haiming; Yu, Zhaomin; Chen, Youlin; Li, Qiumeng; Liang, Fengxia; Chen, Rui (Frontiers in Pharmacology, 2021)
Colorectal cancer (CRC) is one of the most pervasive cancers in the human disease spectrum worldwide, ranked the second most common cause of cancer death by the end of 2020. Prunus mume (PM) is a essential traditional Chinese medicine for the adjuvant treatment of solid tumors, including CRC. In the current study, we utilize means of network pharmacology, molecular docking, and multi-layer experimental verification to research mechanism. The 5 bioactive compounds and a total of 8 critical differentally expressed genes(DEGs) are screened out using bioinformatics approaches of Cytoscape software, String database, GO analysis, KEGG pathways, and molecular docking. RelA has been proved to be highly expressed in CRC. Experiments in vitro has shown that Kaempferol, the main active component of PM, dramatically inhibited the growth, migration and invasion of colorectal cancer cells, and experiments in vivo has shown that PM effectively delays CRC formation and improves the survival cycle of mice. Further analysis shows that PM inhibits the CRC progression by downregulating the expression level of RelA, Bax, Caspase 3, Caspase 9, EGFR in colorectal cancer. PM and its extract are potentially effective therapeutics for the treatment of colorectal cancer via the RelA/ NF-κB signaling pathway.